2016
DOI: 10.1371/journal.pone.0151647
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Physical Activity and Sedentary Behaviour Assessment Questionnaire and the Short-Form International Physical Activity Questionnaire: An Analysis of Health Survey for England Data

Abstract: BackgroundThe Physical Activity and Sedentary Behaviour Assessment Questionnaire (PASBAQ), used within the Health Survey for England (HSE) at 5-yearly intervals, is not included annually due to funding and interview-length constraints. Policy-makers and data-users are keen to consider shorter instruments such as the Short-form International Physical Activity Questionnaire (IPAQ) for the annual survey. Both questionnaires were administered in HSE 2012, enabling comparative assessment in a random sample of 1252 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 48 publications
3
52
0
4
Order By: Relevance
“…The PASBAQ has demonstrated moderate-weak convergent validity in comparison with non-synchronous accelerometry [22]. PASBAQ assesses frequency (number of days in the last 4 weeks) and duration (of an average episode of at least 10 min) in four leisure-time domains [23]:…”
Section: Assessment Of Leisure-time Physical Activitymentioning
confidence: 99%
“…The PASBAQ has demonstrated moderate-weak convergent validity in comparison with non-synchronous accelerometry [22]. PASBAQ assesses frequency (number of days in the last 4 weeks) and duration (of an average episode of at least 10 min) in four leisure-time domains [23]:…”
Section: Assessment Of Leisure-time Physical Activitymentioning
confidence: 99%
“…However, despite such guidelines, population levels of physical activity in children and young people are low. Excluding school based activities, 22% of children aged between 5 and 15 years met the physical activity guidelines of being at least moderately active for at least 60 min every day (23% of boys, 20% of girls) [9]. Several studies have found that physical activity levels differ by ethnicity [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies estimated correlations of 0.23-0.40 between the self-reported data and accelerometer-assessed MVPA [51,54,55]. Questionnaires remain the most feasible method to assess levels of PA at a population level due in part to expensive costs and high respondent burden associated with using device-based methods within large-scale health examination surveys [56].…”
Section: Discussionmentioning
confidence: 99%